Predicting first fall in newly diagnosed Parkinson's disease: Insights from a fall‐naïve cohort. Issue 12 (13th September 2016) - Lord, Sue; Galna, Brook; Yarnall, Alison J.; Coleman, Shirley; Burn, David; Rochester, Lynn
Abstract : Background: Falls are common and associated with reduced independence and mortality in Parkinson's disease. Previous research has been conducted on falls‐prevalent or advanced disease cohorts. Objective: This study identifies risk factors for first fall for 36 months in a newly diagnosed, falls‐naïve cohort. Methods: A total of 121 consecutive Parkinson's disease patients were recruited. Falls data were collected prospectively during 36 months from diagnosis via monthly falls diaries and telephone follow‐up for 117 participants. Assessment comprised a comprehensive battery of clinical, gait, and cognitive measures. Significant predictors were identified from decision‐tree analysis and survival analysis with time to first fall during 36 months as the dependent variable. Findings: At baseline, 26 (22%) participants reported retrospective falls. At 36 months, the remaining cohort (n = 91) comprised 47 fallers (52%) and 30 (33%) nonfallers and 14 (15%) participants with incomplete diaries. Fallers presented with a significantly higher disease severity, poorer ability to stand on one leg, slower gait speed, increased stance time variability, and higher swing time asymmetry. Median time to first fall was 847 days. Gait speed, stance time, and Hoehn & Yahr III stage emerged as significant predictors of first fall, hazard ratio 3.44 (95% confidence interval [CI] 1.58 to 7.48), 3.31(95% CI 1.40 to 7.80), and 2.80 (95% CI 1.38 to 5.65), respectively. The hazard ratio for risk factors combined was 7.82 (CI 2.80 to 21.84). Conclusions: Interventions that target gait deficit and postural control in early Parkinson's disease may limit the potential for first fall. © 2016 International Parkinson and Movement Disorder Society